KEGIATAN SURVEY LAPANGAN UNTUK INVENTARISASI PERMASALAHAN KERUSAKAN PESISIR PANTAI DI KABUPATEN TEGAL, JAWA TENGAH - Muhammad Zikra (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2009)
This paper addresses engineering coastal problems in estuarine and coastal environments based on the results of field measurements. The field survey was conducted on the beach of District of Tegal, Middle East of Java. The practical solutions for these problem are: (1) try to understand the physical system based on available field data; perform new field measurements if the existing field data set is not sufficient; and (2) try to estimate the morphological effects of engineering works based on simple methods (rules of thumb, simplified models, analogy models, i.e. comparison with similar cases elsewhere). The result indicated that engineering coastal works should be designed and constructed along the coastline of District of Tegal, especially at two fisheries ports located at Surodadi village and Kramat village to support and to maintenance economy activity at both areas. Key Words : Coastal problems, Tegal District,